3D Printed Drug Delivery Systems Based on Natural Products - Ángela Aguilar-; Vicente Linares; Marta Casas; Isidoro Caraballo (MDPI AG, 2020)
In the last few years, the employment of 3D printing technologies in the manufacture of drug delivery systems has increased, due to the advantages that they offer for personalized medicine. Thus, the possibility of producing sophisticated and tailor-made structures loaded with drugs intended for tissue engineering and optimizing the drug dose is particularly interesting in the case of pediatric and geriatric population. Natural products provide a wide range of advantages for their application as pharmaceutical excipients, as well as in scaffolds purposed for tissue engineering prepared by 3D printing technologies. The ability of biopolymers to form hydrogels is exploited in pressure assisted microsyringe and inkjet techniques, resulting in suitable porous matrices for the printing of living cells, as well as thermolabile drugs. In this review, we analyze the 3D printing technologies employed for the preparation of drug delivery systems based on natural products. Moreover, the 3D printed drug delivery systems containing natural products are described, highlighting the advantages offered by these types of excipients.